Effects of Previous Wheat Straw on the Yield of Maize in the Oasis Irrigation Region. Issue 6 (28th September 2017) - Yin, Wen; Zhao, Cai; Chai, Qiang; Guo, Yao; Feng, Fuxue; Yu, Aizhong
Abstract : The surface mulch effects on maize ( Zea mays L.) production are not well studied. Higher yield depends on coordinated development among the yield components of crops. The purpose of this study was to determine whether plastic film combined with four straw management systems (no tillage with straw standing [NTSS]; no tillage with straw covering [NTS]; tillage with straw incorporation [TIS]; and conventional tillage without straw retention [CT]) could boost grain yield of maize via increasing leaf area index and yield components. This study was conducted in a wheat ( Triticum aestivum L.)–maize rotation system from 2009 to 2012 in northwestern China. Plastic film combined with straw retention boosted grain yield by 4.5 to 17.5%, especially, NTS had the highest increasing effect, boosted grain yield by 13.7 to 17.5%, and improved harvest index by 5.4 to 8.4%, compared to CT. Plastic film combined with straw retention significantly increased yield components of maize. Among the three straw retention treatments, NTS increased the maize ear number (EN) by 18.1 to 21.0%, increased the kernel number per ear (KNE) by 63.7 to 67.8%, increased the thousand‐kernel weight (TKW) by 8.7 to 9.6%, compared to CT. Straw retention decreased the maize leaf area index (LAI) before the silking stage and increased the LAI after the silking stage, which effectively regulated the growth and development of maize at early and late stages of development, NTS had the best regulating effect. Path analysis indicated that the integrated system with plastic film combined with straw retention increased the maize grain yield by improving the KNE. We conclude that plastic film combined with previous straw covering can be an effective system for boosting crop productivity by improving the yield components and optimizing LAI dynamics under limited resources in arid environments.